Sintesis dan Uji Aktivitas Antimalaria Senyawa Turunan 2,4-Difenil-1,10-Fenantrolin - RUSLIN HADANU; MUSTAFA MUSTAFA; NAZUDIN NAZUDIN (Fakultas Farmasi Universitas Pancasila, 2012)
Malaria is still the main health problems in subtropical and tropical countries. There are 105 countries in the world at malaria endemic and more than 500 million cases or more than 2.7 million deaths from malaria each year. The traditional remedies are no longer effective and the incidence of malarial by P. falciparum, the most dangerous species of parasite, continues to grow, while some traditional drugs such as chloroquine has been resistance. Synthesis of 2,4-diphenyl-1,10-phenanthroline [5] compounds with benzaldehyde [1], acetophenone [2], t-calcone [3], 8-aminoquinoline [4] as starting material through three steps has been carried out. The results of all steps of the reaction were obtained compounds of [5], (1)-N methyl-7,9-diphenyl-1,10-phenanthrolinium sulfate [6] and (1)-N-ethyl-7,9-diphenyl-1,10-phenanthrolinium sulfate [7]. The results of antiplasmodial activity in vitro testing of the derivatives on chloroquine resistant P. falciparum FCR3 indicated that compound [7] has higher antimalarial activity (IC5O = 0.06±0.05 µM) than the activity of [6] compound (ICSO = 1.27±O.97 µM) and [5] compound (1C50 = 1.66±0.70 µM). Results of similar in vitro testing on chloroquine resistant P. falciparum D10 strain indicated that [7] compound has higher antimalarial activity (IC50 = 0.04±0.04 uM) than the activity of [5] compound (IC50 = 1.13±0.30 µM) and [6] compound (ICSO = 0.81±0.06 µM).